Facile pyrolysis preparation of rosin-derived biochar for supporting silver nanoparticles with antibacterial activity. (16th June 2017) - Huang, Jian-Fei; Shi, Qing-Shan; Feng, Jin; Chen, Ming-Jie; Li, Wen-Ru; Li, Liang-Qiu
Abstract: The incorporation of metallic nanoparticles (NPs) into a biomass-based matrix has been intensively investigated because the obtained nanocomposites exhibited effective antibacterial activity to intractable resistance of bacteria. However, the nanocomposites present limitations, such as a multi-step preparation process and a low loading capacity of nanoparticles. A facile preparation route for the preparation of antibacterial metallic nanocomposites would be especially beneficial for industrial fabrication. In this study, we provided a facile strategy for the preparation of a rosin-derived biochar matrix loaded with silver nanoparticles (Ag NPs) as the fillers. The results demonstrated that the preparation of these rosin-derived biochar silver nanocomposites (Rc/Ag nanocomposites) was achieved by a rapid pyrolysis process and a large amount of Ag NPs were in-situ obtained and homogeneously dispersed on the matrix. More importantly, these materials exhibited satisfying antibacterial activities against E. coli and S. aureus. Thus, the Rc/Ag nanocomposites exhibit promising filler for wooden furniture against bacterial infection and could be used as a filter for indoor antibacterial air filtration.